Covid-19, Environmental Engineering and the End of the World as We Know it - Pawłowski, Artur (Problemy Ekorozwoju, 2020)
Covid-19 stopped the World. When all humanity is worried about their health, is there still any room for technical sciences and environmental engineering? In this work, It will be proved, that the answer is yes. Major challenges, such as climate change, are still valid. In addition, being in a quarantine still we have access to clean water and electricity. Without these goods, our lives in these conditions would be much harder. Investments in renewable energy sources are still being carried out. Covid-19 will not bring the end of the World as such, but the end of the World as we know it. Some sectors of the economy (tourism, public transport, in particular air transport) may cease to exist and the service sector will face a deep recession. This means a gigantic economic crisis and retraction of the World development many years back.